If it's not what You are looking for type in the equation solver your own equation and let us solve it.
t in (-oo:+oo)
6*t-9 = -3 // + 3
6*t-9+3 = 0
6*t-6 = 0 // + 6
6*t = 6 // : 6
t = 6/6
t = 1
t = 1
| 7w+4=-52 | | 6+7d=-50 | | -2a+4=20 | | 3n-1=-13 | | -5k+8=58 | | 2k+6=14 | | 9+6t=39 | | 5-6w=-55 | | 2n-10=-24 | | 6m+3=-51 | | 6-5k=26 | | 5(2x-7)=15 | | 4b+8=-28 | | 5n-5=-25 | | 3+6m=51 | | 6m+6=-66 | | k/5=6 | | k-3=-3 | | -4=m-8 | | 7a=84 | | -5b=-60 | | d-6=-14 | | 1=a-6 | | -18=t-9 | | 2+b=4 | | m-7=-1 | | m+3=13 | | t-1=9 | | d+5=4 | | (X+3)x(2x-4)=0 | | x=4*x^2 | | 12-(5x-7)=10x+9 |